Analisis Perancangan Sistem Informasi Reimbursement Transport Berbasis Web Dengan Metode Scrum di Kampus Al Azhar Serpong - Aurellia Prima Agustin; Annisya Walya Doifa; Muhamad Pramuditha; Samso Supriyatna (CV. Multi Kreasi Media, 2025)
The transportation reimbursement process at Al Azhar Serpong Campus is still carried out manually through the completion of transport request forms and the submission of physical supporting documents. This manual procedure has the potential to cause errors in data recording, the risk of losing submitted expense proofs, and requires considerable time during documentation and verification. These conditions lead to an administrative process that is inefficient and not well integrated. This study aims to analyze user needs and design a web-based transportation reimbursement information system that improves efficiency, accuracy, and transparency in the submission, verification, and reporting processes. The research applies the Scrum method, which includes preparing the Product Backlog, conducting Sprint Planning, developing design iterations, carrying out Sprint Reviews to validate designs with users, and performing Sprint Retrospectives to refine the system. The results of this study include a system design represented through UML modeling and user interface prototypes tailored to user needs based on feedback from each Sprint cycle. The proposed system design is expected to improve the reimbursement workflow, reduce administrative errors, accelerate the verification process, and support automatic and structured reporting. Furthermore, the design serves as a foundation for the development of a fully implemented web-based application in future stages.